Lexical transfer between languages enrichment or erosion?: A study of some Chinese dialects in Malaysia - Fook Khoon Wong (Journal of Modern Languages)
It is generally assumed that when there is contact between two societies whose members speak different languages certain linguistic and other cultural changes result, which must be attributed directly to the fact of contact. The phenomenon of language contact, that is, the study of linguistic borrowing has been for a long time an area of great fascination to linguists. Much has been said and written about this phenomenon: the range of variability of the linguistic changes as well as theories behind the changes. Language contact and cultural contact universally result in the transfer of elements from one system to the other by a process which has been variously labelled borrowing or diffusion. This transfer of elements produces systemic change which involves a degree of merging of two separate systems. There can be no denying therefore that linguistic changes result from language contact.